Product of Ap Weight Functions - Parajuli, Vinod; Ghimire, Santosh (Journal of the Institute of Engineering, 2016)
In this paper, we first define Ap weight functions and then show that finite product of weight functions each raised with some power whose sum is one is also an Ap weight function. Journal of the Institute of Engineering, 2015, 11(1): 116-119